Case report: Diagnostic challenges in an adolescent case of autistic catatonia - Nadeem, Nighat J.; Moawad, Abduallah; Howatson, Sophie; Ahmed, Adeel; Cassell, Diana (Frontiers in Psychiatry, 2024)
Catatonia is a complex neuropsychiatric syndrome involving a constellation of psychomotor disturbances including catalepsy, waxy flexibility, stupor, mutism, negativism, agitation, posturing, stereotypes, mannerisms, grimacing, echolalia, and echopraxia. Catatonia occurs in several conditions including psychotic, affective and neurodevelopmental disorders such as autism spectrum disorder (ASD). ASD is a neurodevelopmental disorder characterized by persistent deficits in communication, social interaction, restricted interests, repetitive behaviours and sensory sensitivities.Catatonia can occur in response to life stressors such as extreme fear or threat, interpersonal conflict, tragic events or following significant loss. Those with ASD may be particularly vulnerable to the negative impact of stressors and the link between catatonia and ASD is being increasingly recognized. The overlapping features of catatonia and ASD make it difficult to differentiate often resulting in delayed or missed diagnosis. Catatonia in ASD remains a significant clinical challenge; it is difficult to diagnose and can pose debilitating difficulties for those affected. Catatonia is a treatable condition and prompt recognition is vital in securing the best possible outcome.We report a complex and unique case of a 15-year-old boy who presented with severe cognitive and functional decline with a background history of significant bullying and deterioration in his mental state. This case posed a diagnostic conundrum leading to a diagnosis of underlying ASD, anxiety and trauma.